Simple interface circuit with lead-wire-resistance compensation for single resistive sensors - Petchmaneelumka, Wandee; Julsereewong, Prasit; Julsereewong, Amphawan; Tongpakpanang, Jaturon (My University, 2012)
A simple interface circuit for single resistive sensor-based remote measurements is presented. The realization method using commercially available devices provides not only the output signal linearly related to resistive sensor changes but also the compensation of effect due to lead-wire resistances. Performance of the proposed circuit is confirmed through experimental results. © 2012 ICROS.
Keywords: Interface circuit; Lead-wire-resistance compensation; Remote measurement; Resistive sensor